Компоненти централізації і децентралізації управління галуззю охорони здоров’я - Садовський, Віктор Артемович; Семенченко, Галина Володимирівна; Удовиченко, Наталя Миколаївна (НТУ "ХПІ", 2017)
У статті розглянуті проблеми централізації та децентралізації системи управління в галузі охорони здоров'я. Приведена структура системи управління галуззю охорони здоров’я України. Адміністративні та фінансові заходи по удосконаленню системи охорони здоров’я на різних рівнях ієрархії управління. Пропозиції по удосконаленню структури системи управління галуззю охорони здоров’я. Стан підготовки професійних керівних кадрів для галузі охорони здоров’я. Роль інтелектуального та кадрового менеджменту в державному управлінні охороною здоров’я.

The article discusses the problems of centralization and decentralization of the management system in the field of health protection. The structure of the management system of the healthcare sector of Ukraine is given. Administrative and financial measures to improve the health system at various levels of the hierarchy of management. Functions of the executive bodies of executive power. Proposals for the elimination of contradictions in the system of management functions. Proposals to improve the structure of health care management. Provisions efficiency of the health system. State training professional cadres for health. The role of the intellectual and personnel management in government health care.
Components of centralization and decentralization of health sector
Keywords: система управління; ієрархія; адміністративний вплив; засоби; фінансовий вплив; кадровий менеджмент; centralization; decentralization; hierarchy of the management system; administrative means impact; means of financial impact